Evaluation of bolted CHS flange-plate connections under axial tension. (September 2022) - Fidalgo, Augusto; Packer, Jeffrey A.
Abstract: Over the last five decades, many researchers have performed experiments on bolted circular hollow section flange-plate connections. Most of these tests have been on ring flanges, using small- to medium-size tubes, with far fewer on blank flange plates, and typically under axial tension loading. Herein, all international test data pertaining to bolted flange-plate connections in tension is collated, and supplemented by two more large-scale specimens with blank flange-plate connections. Bolt fracture and flange-plate plastification are the two limit states for bolted flange-plate connections, so the database of 98 tests and 33 numerical models is carefully screened to exclude failure modes that do not pertain to the connection. Prior models for predicting the connection capacity under axial tension are reviewed and evaluated. In addition, a modified T-stub prying model is proposed for circular blank flange-plate connections. The notion of using the flange-plate ultimate stress in connection prying models, instead of the traditional approach of using flange-plate yield stress, is also examined. After a reliability analysis, a preferred design method for blank and ring flange-plate connections is recommended. Highlights: Review of all past tests on bolted CHS flange-plate connections under axial tension. Large-scale, well-instrumented tests reported on blank flange-plate connections. Novel connection design method proposed using a modified T-stub prying model. Design methods investigated using both flange-plate yield and ultimate stress. Practical design recommendations for axially loaded CHS flange-plate connections.